Transcriptome and proteome profile of jejunum in chickens challenged with Salmonella Typhimurium revealed the effects of dietary bilberry anthocyanin on immune function - Zhang, Sheng; Wang, Qin; Ye, Jinling; Fan, Qiuli; Lin, Xiajing; Gou, Zhongyong; Azzam, Mahmoud M.; Wang, Yibing; Jiang, Shouqun (Frontiers in Microbiology, 2023)
Introduction The present study investigated the effects of bilberry anthocyanin (BA) on immune function when alleviating Salmonella Typhimurium (S. Typhimurium) infection in chickens. Methods A total of 180 newly hatched yellow-feathered male chicks were assigned to three groups (CON, SI, and SI + BA). Birds in CON and SI were fed a basal diet, and those in SI + BA were supplemented with 100 mg/kg BA for 18 days. Birds in SI and SI + BA received 0.5 ml suspension of S. Typhimurium (2 × 109 CFU/ml) by oral gavage at 14 and 16 days of age, and those in CON received equal volumes of sterile PBS. Results At day 18, (1) dietary BA alleviated weight loss of chickens caused by S. Typhimurium infection (P < 0.01). (2) Supplementation with BA reduced the relative weight of the bursa of Fabricius (P < 0.01) and jejunal villus height (P < 0.05) and increased the number of goblet cells (P < 0.01) and the expression of MUC2 (P < 0.05) in jejunal mucosa, compared with birds in SI. (3) Supplementation with BA decreased (P < 0.05) the concentration of immunoglobulins and cytokines in plasma (IgA, IL-1β, IL-8, and IFN-β) and jejunal mucosa (IgG, IgM, sIgA, IL-1β, IL-6, IL-8, TNF-α, IFN-β, and IFN-γ) of S. Typhimurium-infected chickens. (4) BA regulated a variety of biological processes, especially the defense response to bacteria and humoral immune response, and suppressed cytokine–cytokine receptor interaction and intestinal immune network for IgA production pathways by downregulating 6 immune-related proteins. Conclusion In summary, the impaired growth performance and disruption of jejunal morphology caused by S. Typhimurium were alleviated by dietary BA by affecting the expression of immune-related genes and proteins, and signaling pathways are related to immune response associated with immune cytokine receptors and production in jejunum.